Prolactin in hypertensive men with androgen deficiency: an eminence grise? - Vizir, V. A.; Nasonenko, O. V.; Demidenko, O. V.; Sadomov, A. S.; Візір, Вадим Анатолійович; Насоненко, Олеся Володимирівна; Деміденко, Олександр Вікторович; Садомов, Антон Сергійович (My University, 2019)
Introduction: Considering significant gap of convincing knowledge in the field of cardiovascular effects of prolactin and its role as a stress hormone in men precise investigations of these peculiarities has become necessary. The aim of this study was to find out the relationship of prolactin concentration with parameters of arterial stiffness in hypertensive men with low testosterone. Materials and methods: In total 83 men were examined including 27 apparently healthy individuals as the control group. Physical examination, ABPM, non-invasive evaluation of arterial stiffness and central hemodynamics parameters, answering AMS questionnaire, evaluation of total testosterone and prolactin levels using ELISA were performed. Results: Initially 56 hypertensive patients were divided into 2 groups with regard to their total testosterone level: group 1 included 31 hypogonadal men, group 2 - 25 male patients who had their testosterone concentrations within the normal range. Prolactin levels appeared to be significantly higher in hypertensive men with lower testosterone, they had more unfavorable parameters of arterial stiffness and the difference between 1 and 2 group in terms of central aoSBP and aoPWV became statistically significant. Prolactin concentration was not related with RWTT and index Aix% 75, a significant correlation was observed between prolactin and aoPWV. A strong correlation was found between prolactin concentration and psychological symptoms in AMS. Conclusion: Our study suggests the positive association of prolactin concentration with psychological domain of andropause symptoms and worse parameters of arterial stiffness among hypertensive men with androgen deficiency.
Keywords: hypertension; androgen deficiency; prolactin; arterial stiffness